The (dis)interest of brazilian students in studying in the current educational context (International Seven Journal of Multidisciplinary, 2023)
The issue of violence at school is just as relevant as the lack of interest in studying that motivates students during the learning process. Motivation is an essential factor for good academic performance. Among other factors, it is necessary to create a stimulating and challenging learning environment where students feel challenged. Motivating students is one of the teacher's daily activities, but parents and specialists must collaborate with affection and encouragement in this process of achievement and progress in studies. The results show that it is possible to bring the world into the classroom and enrich teaching activities through playful practices such as gamification or interactive tableware and digital platforms. These differentiated tools, among others, can stimulate and motivate students to take an interest in school knowledge. This work used the qualitative method through bibliographic research in the Scielo and Google Scholar databases.